1994
DOI: 10.1149/1.2055177
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Structural Properties of SnO2 and Sb : SnO2 Transparent Electrodes with Mixed Electronically Conductive and Ion‐Storage Characteristics

Abstract: Thin SnO2 and Sb-doped SnO2 films have been prepared from aqueous colloidal solutions containing SnCI4 -5H20 and SbCI3 precursors by the dip-coating technique. The films are characterized as small grains (40 to 70 ,&,) and exhibit the ability to uptake reversibly Li + and H + ions from solutions of LiCIO4 (0.1 M) in acetonitrile (AN) or water, LiOH (0.1M) and HCIO4 (0.001 to 0.01M). It was found that Sb-doped (7 a/o Sb) SnO9 films thicker than 100 nm exhibit about three times greater (de)inserted charges as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 7 publications
3
31
1
1
Order By: Relevance
“…Results listed in (Table 3) revealed that films lost their charge capacity, expressed per film thickness (mC/cm2nm), with increasing film thickness, albeit the absolute values of (A Q) are larger for thicker than for thinner films. This has been previously reported for a variety of other electrochromic films [2,3,5,11,13] and is related to the increased compaction of films during repeated heat-treatment. This is not considered as a drawback for Fe/Ti oxide films because single dipped films already exhibit quite large charge capacities which is comparable to NiOx and WO3.…”
Section: Electrochemical and Electrooptical Investigationssupporting
confidence: 70%
See 1 more Smart Citation
“…Results listed in (Table 3) revealed that films lost their charge capacity, expressed per film thickness (mC/cm2nm), with increasing film thickness, albeit the absolute values of (A Q) are larger for thicker than for thinner films. This has been previously reported for a variety of other electrochromic films [2,3,5,11,13] and is related to the increased compaction of films during repeated heat-treatment. This is not considered as a drawback for Fe/Ti oxide films because single dipped films already exhibit quite large charge capacities which is comparable to NiOx and WO3.…”
Section: Electrochemical and Electrooptical Investigationssupporting
confidence: 70%
“…While electrochromic materials and ion conductors have been extensively investigated in the past, much less work has been oriented toward the development of the efficient counter electrode materials. Recently, optically passive counter electrodes based on oxides of tin (SnO2) [2,3], indium (In203) [4], and cerium (CeO2) [5] and corresponding doped or mixed oxide films have been made by the sol-gel route using dip-coating process. The efficient counter-electrode should exhibit a charge capacity in the range 15-25 mC/cm 2 in order to be compatible with WO3 and NiOx [6] active electrochromic films which are commonly used in EC devices.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Sb is considered the best dopant due to its stability. Antimony-doped tin oxide (ATO) is an n-type semiconductor with electrons in the tin 5-based conduction band provided by the antimony dopant [6]. The conductivity and transparency can be controlled by varying the amount of Sb dopant instead of by manipulating the non-stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados m ‡s destacables han sido los obtenidos en -xidos de esta-o (SnO, SnO 2 ) y -xidos mixtos amorfos de esta--o (TCO: Tin Oxide Composites). Aoen cuando en trabajos anteriores se hab'a demostrado que el SnO 2 pod'a insertar peque-as cantidades de litio (4,5), los resultados obtenidos por Idota y col. (3) presentan como gran novedad la capacidad que poseen estos ‡nodos de incorporar hasta 6 ‡tomos de litio por ‡tomo de esta-o, que corresponde a una capacidad espec'fica te-rica de unos 1030 Ah/kg., unas tres veces superior a la que exhibe el carb-n. Aunque la capacidad inicial decrece en torno a un 37 % en los primeros ciclos, la capacidad reversible de almacenaje de litio se estabiliza en valores pr-ximos a 600 Ah/kg, valor que puede mantenerse durante la actuaci-n de la bater'a. Como consecuencia de estas propiedades sobresalientes se ha suscitado un gran interŽs en el estudio de los -xidos de esta-o como materiales an-dicos en bater'as de litio.…”
Section: Introducciînunclassified